A leftward bias for the arrangement of consumer items that differ in attractiveness. Issue 5 (2nd September 2020) - Rodway, Paul; Schepman, Astrid
ABSTRACT: People are frequently biased to use left-side information more than right-side information to inform their perceptual judgements. This research examined whether the leftward bias also applied to preferences for the arrangement of everyday consumer items. Pairs of consumer items were created where one item was more attractive than the other item. Using a two-alternative forced choice task, Experiment 1 found a robust preference for arrangements with the more attractive consumer item on the left side rather than the right side of a pair. Experiment 2 reversed the judgement decision, with participants asked to choose the arrangement they least preferred, and a bias for arrangements with the more attractive item on the right side emerged. Experiment 3 failed to find an effect of the "attractive left" preference on participants' purchasing intentions. The preference for attractive left arrangements has implications for the display of consumer products and for the aesthetic arrangement of objects in general. The findings are discussed in relation to hemispheric asymmetries in processing and the role of left to right scanning.